The Pericope Adulterae, the Gospel of John, and the literacy of Jesus - Keith, Chris (Leiden ; Boston : Brill, 2009)
This book offers a new interpretation and transmission history of the "Pericope Adulterae," arguing that the an interpolator placed the story at John 7.53-8.11 in order to highlight the claim that Jesus could write (John 8.6, 8) in light of a careful reading of John's Gospel.
Foreword (Helen K. Bond); Preface; Abbreviations; Introduction The Most Popular Story in the Gospels; Chapter One A History of Research on John 8.6, 8; Chapter Two Speaking of Writing:?ata??af? and??ap? in Hellenistic, Jewish, and New Testament Contexts; Chapter Three Writing and Gradations of Literacy; Chapter Four Scribal Literacy in the New Testament World: The Scribes (and Pharisees) as Text-Brokers; Chapter Five The Pericope Adulterae at John 7.53-8.11: The Location; Chapter Six The Pericope Adulterae at John 7.53-8.11: The Preceding Context of John 7.
Includes bibliographical references (pages 261-290) and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; Jesus und die Ehebrecherin; Bibel; Jesus Christus; Authorship -- History; Literacy -- Religious aspects -- Christianity; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; Formgeschichte; Literarkritik; Schreib- und Lesefähigkeit; Authorship; Electronic books; Criticism, interpretation, etc; History